2020
DOI: 10.1186/s40101-020-00221-1
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K deficiency, evaluated with higher serum ucOC, was correlated with poor bone status in women

Abstract: Background: An increase in serum undercarboxylated osteocalcin concentrations suggests vitamin K deficiency. Clinical intervention studies suggested that the vitamin K supplementation might contribute to preventing bone loss in postmenopausal women. Evidence on the relationship between serum undercarboxylated osteocalcin (ucOC) levels and bone parameters of quantitative ultrasound (QUS) is limited. We examined the correlation between serum ucOC concentrations and bone status as measured by QUS among middle-age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…We applied Pearson's product-moment correlations to assess for correlation among SI, fat mass, muscle mass, log (25(OH)D), log (TRACP-5b), log (PTH), and grip strength. Multiple linear regression analysis was used to explore the effects of fat mass and muscle mass on SI, with adjustment for age, height, comorbidity, current smoking, alcohol consumption, and exercise (Model 1) [11,28,29]. We added log (25(OH)D), log (TRACP-5b), log (PTH), and grip strength to model 1 (model 2) [30][31][32].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…We applied Pearson's product-moment correlations to assess for correlation among SI, fat mass, muscle mass, log (25(OH)D), log (TRACP-5b), log (PTH), and grip strength. Multiple linear regression analysis was used to explore the effects of fat mass and muscle mass on SI, with adjustment for age, height, comorbidity, current smoking, alcohol consumption, and exercise (Model 1) [11,28,29]. We added log (25(OH)D), log (TRACP-5b), log (PTH), and grip strength to model 1 (model 2) [30][31][32].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Natsumi et al. ( 21 ) revealed that vitamin K deficiency and high serum ucOC were correlated with poor bone status in women. Furthermore, some studies have demonstrated that higher serum ucOC levels were associated with lower BMD in women ( 22 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vergnaud et al (20) found that serum ucOC predicted the risk of hip fracture independent of femoral neck BMD in older women. Natsumi et al (21) revealed that vitamin K deficiency and high serum ucOC were correlated with poor bone status in women. Furthermore, some studies have demonstrated that higher serum ucOC levels were associated with lower BMD in women (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Cholestasis induces VK deficiency and osteoporosis (19). Consequently, VK deficiency elevates the levels of undercarboxylated osteocalcin (ucOC) (20), a marker of bone metabolism. Measurements of BMD and bone metabolic markers are useful for the diagnosis and management of osteoporosis (21,22).…”
Section: Introductionmentioning
confidence: 99%